Anion effects on thermopower of electrochemical systems for low-grade heat harvesting - Li, Xiaoya (2023)
Improvement of the thermopower (α) is essential for enhancing the energy conversion efficiency of a thermally regenerative electrochemical cycle (TREC). Here, we utilize the coordinating nature of anions to modulate the desolvation and reorganization entropy changes during the redox reaction in the aqueous electrochemical system. We show that the preference of anions for an increased α roughly follows the reverse order of the Hofmeister series, with noncoordinating chaotropic anion ClO4- enabling the highest α among the tested anions under the same conditions. Leveraging this finding, we demonstrate a TREC system with a CuHCFe cathode, Fe2+/Fe3+ anode, and ClO4- ion electrolytes and achieve a full-cell α of −3.040 mV K-1. The energy efficiency is 4.1% (27% of the Carnot efficiency) when the cell operates between 10 and 60 °C without heat recuperation. This study provides valuable insights into enhancing α through tailored counterions, highlighting the promising potential of TREC for low-grade energy harvesting.